Corruption, asset origin and the criminal case of money laundering in Indonesian law. Issue 2 (17th August 2021) - Ali, Mahrus; Nurhidayat, Syarif; Prabowo, Muhammad Shidqon; Muhammad, Rusli
Abstract : Purpose: This study aims to investigate Indonesian regulation of Article 69 of the Money Laundering Criminal Act (TPPU) related to proving predicate crimes, as it leaves a debate whether it must be proven beforehand or not. Design/methodology/approach: This research is a normative juridical study, in addition to examining the views of criminal law experts on the formulation of Article 69 of the TPPU Law; it is also extended to the practice of prosecution and court decisions in TPPU cases. Findings: The results of this study show that there are two views related to the obligation to not prove the corruption in the ML case. The first view states that the origin of corruption must be proven, especially because ML is a follow-up crime, so it is necessary to prove corrosive crime as one of the predicate offenses. The second view states that the predicate offense of corruption does not have to be proven beforehand because TPPU is an independent offense. Originality/value: This research focuses on analyzing whether or not it is obligatory to prove the original crime of corruption in the money laundering case.